2017
DOI: 10.3389/fpls.2017.02090
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mapping of PMR1, a Novel Locus Conferring Resistance to Powdery Mildew in Pepper (Capsicum annuum)

Abstract: Powdery mildew, caused by Leveillula taurica, is a major fungal disease affecting greenhouse-grown pepper (Capsicum annuum). Powdery mildew resistance has a complex mode of inheritance. In the present study, we investigated a novel powdery mildew resistance locus, PMR1, using two mapping populations: 102 ‘VK515' F2:3 families (derived from a cross between resistant parental line ‘VK515R' and susceptible parental line ‘VK515S') and 80 ‘PM Singang' F2 plants (derived from the F1 ‘PM Singang' commercial hybrid). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…Nucleotide-binding site leucine-rich repeat (NBS-LRR) genes constitute the largest family of R genes. NBS-LRR genes are associated with resistance to powdery and downy mildew pathogens in several species, including Arabidopsis (Warren et al 1998), wheat (He et al 2018), barley (Wei et al 1999; Zhou et al 2001), pepper (Jo et al 2017), and grapes (Riaz et al 2011; Zini et al 2019). We divided the NBS-LRR genes into eight different classes depending on the domains detected in the proteins: CC-NBS-LRR, CC-NBS, CC-X, TIR-NBS-LRR, TIR-NBS, TIR-X, NBS-LRR, NBS (called hereafter NBS-LRR when described as a whole).…”
Section: Resultsmentioning
confidence: 99%
“…Nucleotide-binding site leucine-rich repeat (NBS-LRR) genes constitute the largest family of R genes. NBS-LRR genes are associated with resistance to powdery and downy mildew pathogens in several species, including Arabidopsis (Warren et al 1998), wheat (He et al 2018), barley (Wei et al 1999; Zhou et al 2001), pepper (Jo et al 2017), and grapes (Riaz et al 2011; Zini et al 2019). We divided the NBS-LRR genes into eight different classes depending on the domains detected in the proteins: CC-NBS-LRR, CC-NBS, CC-X, TIR-NBS-LRR, TIR-NBS, TIR-X, NBS-LRR, NBS (called hereafter NBS-LRR when described as a whole).…”
Section: Resultsmentioning
confidence: 99%
“…Necrotic and chlorotic leaf spotting reported by Jørgensen (1992) is similar to the HR characteristics observed in this study. In an investigation into accumulation of H 2 O 2 because of loss-of-function of mlo gene, Piffanelli et al (2002) reported a (Jo et al, 2017). It would be worthwhile to screen the evaluated material in this study with the PMR1 marker.…”
Section: Discussionmentioning
confidence: 97%
“…The first attempt to map powdery mildew resistance was carried out by Lefebvre and colleagues, which described the quantitative nature of the resistance identifying a robust Quantitative Trait Locus (QTL) on chromosome 6 (Lt 6.1), and reported epistatic interactions explaining more than 50% of the genotypic variance [18] (Table 2). A single dominant locus, PMR1, located in a syntenic region of 4 Mb of pepper Chr 4 and responsible for the powdery mildew resistance has been reported [19]. Within this locus, two genes across the 622 predicted ones were found to share sequence similarity to the nucleotide-binding site leucine-rich repeat domain containing R proteins (NBS-LRR), which represent clusters of resistance genes in plants.…”
Section: Bacterial Spot Of Peppermentioning
confidence: 99%